RETRACTED: Research of materials for clothing in the production of various sewing products - Mamatkulova Saida; Tursumatova Shakhlo; Turdiyev Makhmudjon; Abdurakhimova Manzura; Abdullayev Makhmudjon; Berdiyeva Rano (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001